Physical properties of Malaysian coffee bean (Coffea Liberica) - Ismail, Iryane; Anuar, Mohd Shamsul; Shamsudin, Rosnah (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
In Malaysia, Liberica coffee is the most important coffee species grown in Malaysia. However, there is little or none at all research on coffee bean since the plant itself is a low income crop. Therefore, research on Liberica coffee can help to increase the knowledge of coffee farmers or coffee manufacturers in the processing and handling of the coffee beans. In this study, the physical properties of Liberica coffee beans were studied. The properties investigated include the size, mass, density, color and water activity. Green coffee beans used were processed by dry method where the crushed coffee berries were sun-dried for 7-21 days depending on the climate. The coffee beans were directly evaluated for their physical properties without any special treatment. Working environment temperature was approximately 27 °C. The initial moisture content of the beans is 13.85%. The measured values of length, thickness and width are 11.46, 4.53 and 7.54 mm respectively. The average bean mass was found to be 0.212 gm. Bulk density is 639.89 kg/m3. The color value of L*, a* and b* are 35.72, +7.28 and +22.06. The water activity has been determined as 0.663. The properties measured are important parameters to the quality and marketability of the coffee beans.